Czy minimalizm w teorii prawdy prowadzi do relatywizmu? - Derra-Włochowicz, Aleksandra (Filozofia Nauki, 2003)
The author considers the problem of relation between the so called minimalist theories of truth and relativism in philosophy - trying to answer the question: Does minimalism in the theory of truth result in relativism? In order to make the above question more precise, the author takes two steps. Initially, she defines minimalism (deflationism) with respect to truth in philosophy, enumerates various theories which are counted as deflationary and submits basic claims of deflationary views trying to find their theoretical hard-core. She takes Paul Horwich's deflationary theory of truth as a representative example of minimalist approaches and present the goals which Horwich is trying to reach in this theory. She points out its elementary assumption and Horwich's solution to the problem of truth. Afterwards, the author confronts the problem of relativism. Firstly, she distinguishes various ways of understanding the very notion of 'relativism'. Secondly, she points out what kind of relativism can be dangerous (and why) in philosophy. Finally, she concludes that minimalism in the theory of truth does not result in such philosophically dangerous standpoint.